Living with autism: The experience of developmentally healthy adolescents and youths who have a sibling diagnosed with autism spectrum disorder - Michel, Jessica (2019)
Researchers have proposed that typically developing siblings of individuals diagnosed with autism spectrum disorder (ASD), or target siblings, are at increased risk of experiencing psychological distress particularly when compared to other clinical and community sibling groups. To date, evidence drawn from quantitative studies, utilising the target siblings’ mothers as the primary informants has been mixed. These studies have primarily focused on risk factors, while the role of protective factors in the experiences of target siblings remains unexplored in quantitative investigations. However, qualitative studies utilising target siblings as informants have emerged providing insights regarding the processes of coping and adaptation that target siblings and their families employ. Therefore, this mixed methods (quantitative and qualitative), multi-informant study sought to explore the role of risk and protective factors in the experiences of target siblings aged between 12 and 24 years (M = 16.58 years, SD = 3.10 years) utilising a two stage design. The two purposes of Stage One were to examine if target siblings were more distressed than community siblings as reported by the siblings themselves and their mothers on measures of psychological distress, and the protective factors of psychological resilience and family functioning; as well as to determine the role of psychological resilience and family functioning on the level of psychological distress in the target siblings. In the first part of Stage One 52 target siblings reported significantly lower levels of psychological resilience (large effect) when compared to 34 community siblings. No significant differences were detected on the measures of psychological distress (small effect) and family functioning (small effect) between the two groups of siblings. The mothers reported that target siblings displayed significantly lower levels of psychological resilience (medium effect) and significantly greater levels of psychological distress (medium effect) when compared to the reports of the mothers of the community siblings. The mothers of the target siblings reported similar levels of family functioning (small effect) when compared to the mothers of the community siblings. Using a hierarchical regression analysis family functioning and psychological resilience were identified as significant predictors of psychological distress in the target siblings. Greater family dysfunction was associated with greater psychological distress in the target siblings while higher levels of psychological resilience in the target siblings were associated with lower levels of psychological distress. In sum, the degree of discrepancy between the experiences of the target siblings and community siblings seemed to vary based on the domains measured as well as on the type of informant (i.e., siblings vs. mothers). However, the psychological distress experienced by target siblings was influenced by their psychological resilience and degree of family functioning. In Stage Two, a qualitative methodology employing a phenomenological approach was adopted in order to investigate the lived experiences of target siblings and the factors that shaped these experiences. Twelve target siblings and their mothers, who had participated in Stage One, were interviewed separately and two set of themes emerged from the analysis; one from the interviews with the target siblings, and one from the interviews with their mothers. The narratives of the target siblings clustered around three main themes: (i) the evolving natures of the target siblings’ experiences; (ii) the challenges experienced by the target siblings; and (iii) the role of target siblings as carers. The narratives of the target siblings’ mothers yielded four main themes: (i) the impact raising children with ASD had on the family unit; (ii) the impact living with children with ASD had on the target siblings; (iii) the nature of the target siblings’ interpersonal experiences; and (iv) the developmental maturation of the target siblings. Thus, the main factors that shaped the target siblings’ experiences based on the narratives of the target siblings and their mothers were the target siblings’ developmental stage, the target siblings’ interpersonal experiences, the role of the target siblings within the family unit, and the needs of the family unit. In conclusion, the results of Stages One and Two indicated that living with brothers or sisters with ASD had a pervasive impact on the target siblings, influencing the experiences of target siblings in psychological, interpersonal, and familial domains. Given that target siblings appeared to have limited psychological resources to cope with the various challenges they encounter the results of the present study are of clinical significance. The complex, multi-faceted, evolving nature of the target siblings’ experiences indicate that clinicians supporting target siblings can benefit from conceptualising the experiences of this population within a risk and protective factor framework that considers psychological resilience, as well as familial and developmental factors as influential aspects that shape the psychological adjustment of the target siblings